Cooccurring Gentiana verna and Gentiana acaulis and Their Neighboring Plants in Two Swiss Upper Montane Meadows Harbor Distinct Arbuscular Mycorrhizal Fungal Communities - Sýkorová, Zuzana; Wiemken, Andres; Redecker, Dirk (Applied and Environmental Microbiology, 2007)
The community composition of arbuscular mycorrhizal fungi (AMF) was analyzed in roots of Gentiana verna, Gentiana acaulis, and accompanying plant species from two species-rich Swiss alpine meadows located in the same area. The aim of the study was to elucidate the impact of host preference or host specificity on the AMF community in the roots. The roots were analyzed by nested PCR, restriction fragment length polymorphism screening, and sequencing of ribosomal DNA small-subunit and internal transcribed spacer regions. The AMF sequences were analyzed phylogenetically and used to define monophyletic sequence types. The AMF community composition was strongly influenced by the host plant species, but compositions did not significantly differ between the two sites. Detailed analyses of the two cooccurring gentian species G. verna and G. acaulis, as well as of neighboring Trifolium spp., revealed that their AMF communities differed significantly. All three host plant taxa harbored AMF communities comprising multiple phylotypes from different fungal lineages. A frequent fungal phylotype from Glomus group B was almost exclusively found in Trifolium spp., suggesting some degree of host preference for this fungus in this habitat. In conclusion, the results indicate that within a relatively small area with similar soil and climatic conditions, the host plant species can have a major influence on the AMF communities within the roots. No evidence was found for a narrowing of the mycosymbiont spectrum in the two green gentians, in contrast to previous findings with their achlorophyllous relatives.